Halide solid electrolyte material containing doped metal as well as preparation and application of halide solid electrolyte material

Aluminum-doped lithium hafnium chloride electrolytes address the cost and performance limitations of rare earth halides by enhancing ion conductivity and stability, facilitating scalable production of solid-state batteries.

CN120280537APending Publication Date: 2025-07-08SOUTHERN UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510265665.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-06
Publication Date
2025-07-08

AI Technical Summary

Technical Problem

Existing solid-state electrolytes, particularly those based on rare earth metal halides like Li3YCl6, are costly due to the scarcity of these elements and have suboptimal ion transport properties, limiting their scalability and performance in solid-state batteries.

Method used

Introduce aluminum (Al3+) doping into lithium hafnium chloride (Li2HfCl6) to form Li2+xAlxHf1-xCl6, optimizing the ratio of Al and Hf to enhance ion conductivity and reduce production costs, using a ball-milling process that avoids high-temperature annealing.

Benefits of technology

The Al-doped electrolytes exhibit improved ion conductivity, capacity, and cycling stability, reducing production costs and expanding their applicability, while maintaining cost-effectiveness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120280537A_ABST
    Figure CN120280537A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of electrolyte materials, in particular to a halide solid electrolyte material containing doped metal and preparation and application of the halide solid electrolyte material. The invention provides the halide solid electrolyte material containing the doped metal, the structural formula of the halide solid electrolyte material containing the doped metal is shown as Li < 2 + x > Al < x > Hf < 1-x > Cl < 6 >, and x is greater than or equal to 0.1 and less than or equal to 0.4. By optimizing the content of an aluminum element and the content of a hafnium element in the solid electrolyte material and partially replacing Hf < 4 + > with a heterovalent metal Al < 3 + >, although a lattice gap is reduced, more Li < + > is introduced into a lattice, so that the transmission efficiency of Li < + > is higher, and the purposes of improving the ionic conductivity, the capacity and the cycling stability are achieved; and the content of Al metal in the earth crust is rich, so that the cost is low, the production cost can be further reduced, and the wide application rate of the product can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the technical field of electrolyte materials, and particularly relates to a halide solid electrolyte material containing doped metal, and its preparation and application. Background Art

[0002] Lithium-ion batteries have strong competitiveness in the energy storage field due to their high specific energy, long service life and other advantages. In recent years, lithium-ion batteries have played an increasingly important role in human society. Whether in various electronic product fields such as mobile phones or in the transportation field, the research and production of lithium-ion batteries have advanced by leaps and bounds. Traditional lithium-ion batteries face several major problems. For example, due to the use of flammable organic liquid electrolytes, safety problems such as explosions caused by side reactions or volatilization during charging / discharging are inevitable; and when working in a low-temperature environment, the viscosity of the electrolyte increases due to the low temperature, resulting in an increase in impedance and a decrease in ionic conductivity. On the other hand, traditional lithium batteries using insertion electrodes such as graphite anodes and oxide cathodes can no longer meet the growing demand for energy density.

[0003] In order to overcome the problems faced by existing commercial liquid lithium-ion batteries, all-solid-state batteries (ASSBs) based on solid electrolytes have received extensive attention in recent years due to their inherent safety performance and high energy density, and are regarded as the most promising candidates for next-generation energy storage.

[0004] Currently, the common solid electrolytes are as follows: sulfides, oxides, halides, polymers. Oxides have good electrochemical stability and a relatively wide electrochemical window, but due to their rigidity and brittleness, the electrolyte and the electrode cannot fit well, resulting in an increase in interfacial impedance, and their high electronic conductivity also promotes the formation of lithium dendrites and the growth of dendrites along grain boundaries; sulfides have relatively high ionic conductivity, but a narrow electrochemical window and unstable chemical properties, and are prone to decomposing harmful gases such as hydrogen sulfide; polymer electrolytes have good toughness and processability, but low ionic conductivity. Halides have relatively high ionic conductivity and can also exist stably in dry gases, and are considered to be one of the best candidates for realizing all-solid-state technology. Among them, the most widely discussed category of halide solid electrolytes is Li a MCl6 type, and M is mostly rare earth elements such as Y, Ho, Sc, In, etc. However, due to the relatively small content of these elements on the earth, they are extremely expensive, resulting in too high a cost of rare earth halide electrolytes and unable to be mass-produced.

[0005] Therefore, a method of isovalent substitution of rare earth halides by tetravalent metal ions has been developed to reduce the content of rare earth elements, thereby reducing costs and relatively improving their conductivity. There are relevant reports suggesting that the tetravalent metal Hf 4+It is doped into Li3YCl6 by ball milling, and its conductivity is significantly improved. The same doping method of heterovalent substitution is also applicable to halides of tetravalent central metals such as Li2MCl6 (M = Hf, Zr). The electrolytes of tetravalent central metal halides have a lower cost and a poorer conductivity compared to rare earth halides. Therefore, improving the ion transport performance of tetravalent central metal halides by the above method while ensuring the cost is also one of the research directions of halides at present.

[0006] In addition to doping with tetravalent metal halides, there is an urgent need to provide a scheme that can combine heterovalent metals with tetravalent metals to effectively enhance the ion transport performance of tetravalent metal-based halide electrolytes while maintaining their cost-effectiveness. Summary of the Invention

[0007] The purpose of this application is to provide a halide solid electrolyte material containing doped metals and its preparation and application, aiming to regulate the proportion of doped metals in the solid electrolyte material to obtain a solid electrolyte material with excellent performance.

[0008] To achieve the above application purpose, the technical solution adopted in this application is as follows:

[0009] In the first aspect, this application provides a halide solid electrolyte material containing doped metals. The structural formula of the halide solid electrolyte material containing doped metals is as shown in Li 2+x Al x Hf 1-x Cl6, where 0.1 ≤ x ≤ 0.4.

[0010] In some embodiments, in the halide solid electrolyte material containing doped metals, the molar ratio of Al element to Hf element is 0.1 - 0.4:0.6 - 0.9.

[0011] In some embodiments, in the halide solid electrolyte material containing doped metals, the molar ratio of Al element to Hf element includes 0.1:0.9, 0.2:0.8, 0.3:0.7, 0.4:0.6.

[0012] In some embodiments, the halide solid electrolyte material containing doped metals includes Li 2.1 Al 0.1 Hf 0.9 Cl6, Li 2.2 Al 0.2 Hf 0.8 Cl6, Li 2.3 Al 0.3 Hf 0.7 Cl6, Li 2.4 Al 0.4 Hf 0.6 Cl6, any one of them.

[0013] In a second aspect, the present application provides a method for preparing a doped-metal-containing halide solid electrolyte material, comprising the following steps:

[0014] Weigh a certain amount of a lithium-containing compound, a hafnium-containing compound, and an aluminum-containing compound, and perform a first ball milling treatment to obtain a first mixture;

[0015] Perform a second ball milling treatment on the first mixture to obtain a doped-metal-containing halide solid electrolyte material.

[0016] In some embodiments, in the step of the first ball milling treatment, it includes the following: After mixing the lithium-containing compound, the hafnium-containing compound, and the aluminum-containing compound, place them in a ball milling jar and perform a manual first ball milling treatment for 30 minutes.

[0017] In some embodiments, in the step of the second ball milling treatment, it includes the following: After mixing the first mixture with a dispersant and ball milling beads, place them in a ball milling jar and perform a second ball milling treatment.

[0018] In some embodiments, the rotation speed of the second ball milling treatment is 400 - 500 rpm, and the ball milling time is 10 - 12 hours.

[0019] In some embodiments, the ball milling beads are selected from ZrO2 ball milling beads, and the ball-to-material ratio of the ZrO2 ball milling beads to the first mixture is 40:1 - 1.2.

[0020] In a third aspect, the present application provides a solid-state battery. The solid-state battery includes a positive electrode material, a negative electrode material, a separator, and a solid electrolyte. Among them, the solid electrolyte is selected from a doped-metal-containing halide solid electrolyte material or is prepared by the method for preparing a doped-metal-containing halide solid electrolyte material.

[0021] The doped-metal-containing halide solid electrolyte material provided in the first aspect of the present application has a structural formula of Li 2+x Al x Hf 1-x Cl6 as shown, where 0.1 ≤ x ≤ 0.4. By optimizing the content of aluminum element and hafnium element in the solid electrolyte material, using the hetero-valent metal Al 3+ to partially replace Hf 4+ , although the lattice gap is reduced, more Li + enters the lattice, making the Li + transport efficiency higher, thereby achieving the purpose of improving ionic conductivity, capacity, and cycle stability. And because the Al metal is rich in the earth's crust and has a low cost, it is beneficial to further reduce the production cost and can increase the wide application rate of the product.

[0022] The preparation method of the halide solid electrolyte material containing doped metal provided in the second aspect of the present application is a synthesis method that first performs manual ball milling treatment and then high-energy ball milling treatment. This synthesis method is easy to operate and does not require high-temperature annealing, further saving energy costs. At the same time, the ball milling treatment can effectively shorten the reaction time, which is beneficial to the wide application of this preparation method.

[0023] The solid-state battery provided in the third aspect of the present application includes a positive electrode material, a negative electrode material, a separator, and a solid electrolyte. Among them, the solid electrolyte is selected from the halide solid electrolyte material containing doped metal or is prepared by the preparation method of the halide solid electrolyte material containing doped metal. Since the provided halide solid electrolyte material containing doped metal has excellent ionic conductivity, capacity, and cycle stability, the obtained solid-state battery has excellent properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the following will briefly introduce the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings in the following description are only some embodiments of the present application. For those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative efforts.

[0025] Figure 1 It is a low-magnification SEM image of the Al-doped Li 2.1 Al 0.1 Hf 0.9 Cl6 solid electrolyte material obtained in Example 1 of the present invention.

[0026] Figure 2 It is a high-magnification SEM image of the Al-doped Li 2.1 Al 0.1 Hf 0.9 Cl6 solid electrolyte material obtained in Example 1 of the present invention.

[0027] Figure 3 It is the xrd pattern of Al-doped Li 2+x Al x Hf 1-x Cl6 (x = 0.1, 0.2, 0.3, 0.4) obtained in Example 1 of the present invention.

[0028] Figure 4 It is the impedance spectrum of Al-doped Li 2+x Al x Hf 1-x Cl6 (x = 0.1, 0.2, 0.3, 0.4) obtained in Example 1 of the present invention.

[0029] Figure 5The Li 2.1 Al 0.1 Hf 0.9 charge-discharge curves of the all-solid-state battery with Cl6 solid electrolyte material obtained in Example 1 of the present invention.

[0030] Figure 6 The Li 2.1 Al 0.1 Hf 0.9 rate performance of the all-solid-state battery with Cl6 solid electrolyte material obtained in Example 1 of the present invention.

[0031] Figure 7 The Li 2.1 Al 0.1 Hf 0.9 cycle stability of the all-solid-state battery with Cl6 solid electrolyte material obtained in Example 1 of the present invention. Detailed implementation manners

[0032] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application clearer, the present application will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0033] In the present application, the term "and / or" describes the relationship between associated objects and indicates that three relationships may exist. For example, A and / or B may indicate: A exists alone, A and B exist simultaneously, and B exists alone. Wherein A and B may be singular or plural. The character " / " generally indicates that the associated objects before and after are in an "or" relationship.

[0034] In the present application, "at least one" means one or more, and "a plurality" means two or more. "At least one of the following items (pieces)" or its similar expression refers to any combination of these items, including any combination of single item (piece) or plural items (pieces). For example, "at least one of a, b, or c", or, "at least one of a, b, and c" can all represent: a, b, c, a-b (that is, a and b), a-c, b-c, or a-b-c, where a, b, and c can be single or multiple respectively.

[0035] It should be understood that in various embodiments of the present application, the magnitude of the sequence numbers of the above processes does not mean the order of execution. Some or all steps may be executed in parallel or sequentially. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation to the implementation process of the embodiments of the present application.

[0036] The terms used in the embodiments of the present application are for the purpose of describing specific embodiments only and are not intended to limit the present application. The singular forms "a" and "the" used in the embodiments of the present application and the appended claims are also intended to include the plural forms unless the context clearly indicates otherwise.

[0037] The weight of the relevant components mentioned in the specification of the embodiments of the present application may not only refer to the specific content of each component, but also represent the proportional relationship of the weights between the components. Therefore, as long as the content of the relevant components in the specification of the embodiments of the present application is enlarged or reduced in proportion, it is within the scope disclosed in the specification of the embodiments of the present application. Specifically, the mass in the specification of the embodiments of the present application may be mass units well-known in the chemical field such as μg, mg, g, kg, etc.

[0038] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and cannot be understood as indicating or implying relative importance or implicitly specifying the quantity of the indicated technical features. For example, without departing from the scope of the embodiments of the present application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Thus, the features defined with "first" and "second" may explicitly or implicitly include one or more of such features.

[0039] In a first aspect of the embodiments of the present application, a doped-metal halide solid electrolyte material is provided. The structural formula of the doped-metal halide solid electrolyte material is as shown in Li 2+x Al x Hf 1-x Cl6, where 0.1 ≤ x ≤ 0.4.

[0040] The doped-metal halide solid electrolyte material provided in the first aspect of the embodiments of the present application has a structural formula as shown in Li 2+x Al x Hf 1-x Cl6, where 0.1 ≤ x ≤ 0.4. By optimizing the content of aluminum element and hafnium element in the solid electrolyte material, using the hetero-valent metal Al 3+ to partially replace Hf 4+ , although the lattice gap is reduced, more Li + is introduced into the lattice, making the Li + transport efficiency higher, so as to achieve the purpose of improving ionic conductivity, capacity and cycle stability. And because the Al metal is rich in the earth's crust and has a low cost, it is beneficial to further reduce the production cost and can increase the wide application rate of the product.

[0041] In some embodiments, in the doped-metal-containing halide solid electrolyte material, the molar ratio of Al element to Hf element is 0 to 0.4:0.6 to 1. By regulating the appropriate ratio of Al and Hf, the highest ionic conductivity and the trend of conductivity change are obtained, and the performance of the full cell is improved.

[0042] In some embodiments, in the doped-metal-containing halide solid electrolyte material, the molar ratio of Al element to Hf element includes 0:1, 0.1:0.9, 0.2:0.8, 0.3:0.7, 0.4:0.6.

[0043] In some embodiments, the doped-metal-containing halide solid electrolyte material includes any one of Li2HfCl6, Li 2.1 Al 0.1 Hf 0.9 Cl6, Li 2.2 Al 0.2 Hf 0.8 Cl6, Li 2.3 Al 0.3 Hf 0.7 Cl6, Li 2.4 Al 0.4 Hf 0.6 Cl6.

[0044] The second aspect of the embodiments of the present application provides a preparation method of a doped-metal-containing halide solid electrolyte material, including the following steps:

[0045] S01. Weigh a certain amount of lithium-containing compound, hafnium-containing compound, and aluminum-containing compound and perform the first ball milling treatment to obtain a first mixture;

[0046] S02. Perform the second ball milling treatment on the first mixture to obtain a doped-metal-containing halide solid electrolyte material.

[0047] The preparation method of the doped-metal-containing halide solid electrolyte material provided in the second aspect of the embodiments of the present application is a synthesis method that first performs manual ball milling treatment and then high-energy ball milling treatment. This synthesis method is easy to operate and does not require high-temperature annealing, further saving energy costs. At the same time, the ball milling treatment can effectively shorten the reaction time, which is beneficial to the wide application of this preparation method.

[0048] In step S01, weigh a certain amount of lithium-containing compound, hafnium-containing compound, and aluminum-containing compound and perform the first ball milling treatment to obtain a first mixture.

[0049] In some embodiments, the lithium-containing compound is selected from lithium chloride; the hafnium-containing compound is selected from hafnium chloride; the aluminum-containing compound is selected from aluminum chloride.

[0050] In some specific embodiments, the aluminum-containing compound is selected from anhydrous aluminum chloride (AlCl3); the hafnium-containing compound is selected from hafnium chloride (HfCl4); the aluminum-containing compound is selected from lithium chloride (LiCl).

[0051] In some embodiments, in the step of the first ball milling treatment, the following is included: after mixing the lithium-containing compound, the hafnium-containing compound, and the aluminum-containing compound, place them in a ball milling jar and perform manual first ball milling treatment for 30 minutes.

[0052] In step S02, the first mixture is subjected to a second ball milling treatment to obtain a doped metal-containing halide solid electrolyte material.

[0053] In some embodiments, in the step of the second ball milling treatment, the following is included: after mixing the first mixture with a dispersant and ball milling beads, place them in a ball milling jar and perform the second ball milling treatment.

[0054] In some embodiments, the rotation speed of the second ball milling treatment is 400 - 500 rpm, and the ball milling time is 10 - 12 hours.

[0055] In some specific embodiments, the rotation speed of the second ball milling treatment includes but is not limited to typical but non-limiting values such as 400 rpm, 410 rpm, 420 rpm, 430 rpm, 440 rpm, 450 rpm, 460 rpm, 470 rpm, 480 rpm, 490 rpm, 500 rpm, etc.

[0056] In some specific embodiments, the ball milling time of the second ball milling treatment includes but is not limited to typical but non-limiting values such as 10 hours, 10.5 hours, 11 hours, 11.5 hours, 12 hours, etc.

[0057] In some embodiments, the ball milling beads are selected from ZrO2 ball milling beads, and the ball-to-material ratio of the ZrO2 ball milling beads to the first mixture is 40:1 - 1.2.

[0058] In some specific embodiments, the ball-to-material ratio of the ZrO2 ball milling beads to the first mixture is 40:1.

[0059] The third aspect of the embodiments of the present application provides a solid-state battery. The solid-state battery includes a positive electrode material, a negative electrode material, a separator, and a solid electrolyte. Among them, the solid electrolyte is selected from a doped metal-containing halide solid electrolyte material or is prepared by a preparation method of a doped metal-containing halide solid electrolyte material.

[0060] The solid-state battery provided in the third aspect of the embodiments of the present application includes a positive electrode material, a negative electrode material, a separator, and a solid electrolyte. Among them, the solid electrolyte is selected from a halide solid electrolyte material containing a doped metal or is prepared by a preparation method of a halide solid electrolyte material containing a doped metal. Since the provided halide solid electrolyte material containing a doped metal has excellent ionic conductivity, capacity, and cycle stability, the obtained solid-state battery has excellent properties.

[0061] The following is an illustration with specific embodiments.

[0062] Example 1

[0063] A Li 2.1 Al 0.1 Hf 0.9 Cl6 solid electrolyte material, and the specific preparation steps are as follows:

[0064] ① Manual grinding: Weigh a certain amount of LiCl, HfCl4, and AlCl3 and pour them into an agate ball milling jar for grinding for 30 minutes.

[0065] ② High-energy ball milling: Transfer the above-ground sample into a silicon carbide ball milling jar, and at the same time measure a certain amount of organic dispersant and add it to the ball milling jar. Select appropriate ZrO2 ball milling beads and put them into the ball milling jar. The ball-to-material ratio of the ZrO2 ball milling beads to the material is 40:1. Assemble the ball milling jar into a planetary ball mill and run it at a speed of 500 rpm for 10 - 12 hours.

[0066] Example 2

[0067] A Li 2.1 Al 0.2 Hf 0.8 Cl6 solid electrolyte material, and the specific preparation steps are as follows:

[0068] ① Manual grinding: Weigh a certain amount of LiCl, HfCl4, and AlCl3 and pour them into an agate ball milling jar for grinding for 30 minutes.

[0069] ② High-energy ball milling: Transfer the above-ground sample into a silicon carbide ball milling jar, and at the same time measure a certain amount of organic dispersant and add it to the ball milling jar. Select appropriate ZrO2 ball milling beads and put them into the ball milling jar. The ball-to-material ratio of the ZrO2 ball milling beads to the material is 40:1. Assemble the ball milling jar into a planetary ball mill and run it at a speed of 500 rpm for 10 - 12 hours.

[0070] Example 3

[0071] A Li 2.1 Al 0.3 Hf 0.7 Cl6 solid electrolyte material, and the specific preparation steps are as follows:

[0072] ① Manual grinding: Weigh a certain amount of LiCl, HfCl4, and AlCl3 and pour them into an agate ball mill jar for grinding for 30 minutes.

[0073] ② High-energy ball milling: Transfer the ground sample above into a silicon carbide ball mill jar. At the same time, measure a certain amount of organic dispersant and add it to the ball mill jar. Select appropriate ZrO2 ball milling beads and put them into the ball mill jar. The ball-to-material ratio of ZrO2 ball milling beads is 40:1. Assemble the ball mill jar into a planetary ball mill and run it at a speed of 500 rpm for 10 - 12 hours.

[0074] Example 4

[0075] A kind of Li 2.1 Al 0.4 Hf 0.6 Cl6 solid electrolyte material, and the specific preparation steps are as follows:

[0076] ① Manual grinding: Weigh a certain amount of LiCl, HfCl4, and AlCl3 and pour them into an agate ball mill jar for grinding for 30 minutes.

[0077] ② High-energy ball milling: Transfer the ground sample above into a silicon carbide ball mill jar. At the same time, measure a certain amount of organic dispersant and add it to the ball mill jar. Select appropriate ZrO2 ball milling beads and put them into the ball mill jar. The ball-to-material ratio of ZrO2 ball milling beads is 40:1. Assemble the ball mill jar into a planetary ball mill and run it at a speed of 500 rpm for 10 - 12 hours.

[0078] Comparative Example 1

[0079] A kind of Li2HfCl6 solid electrolyte material, and the specific preparation steps are as follows:

[0080] ① Manual grinding: Weigh a certain amount of LiCl and HfCl4 and pour them into an agate ball mill jar for grinding for 30 minutes.

[0081] ② High-energy ball milling: Transfer the ground sample above into a silicon carbide ball mill jar. At the same time, measure a certain amount of organic dispersant and add it to the ball mill jar. Select appropriate ZrO2 ball milling beads and put them into the ball mill jar. The ball-to-material ratio of ZrO2 ball milling beads is 40:1. Assemble the ball mill jar into a planetary ball mill and run it at a speed of 500 rpm for 10 - 12 hours.

[0082] Performance test

[0083] (1) The Li 2.1 Al 0.1 Hf 0.9The Cl6 solid electrolyte materials were analyzed by scanning electron microscopy at low magnification and high magnification, and the solid electrolyte materials obtained in Examples 1 to 4 were analyzed by X-ray diffraction.

[0084] (2) The solid electrolyte materials obtained in Examples 1 to 4 were subjected to impedance analysis.

[0085] (3) Assembly and performance testing of lithium-ion all-solid-state batteries

[0086] The solid electrolyte material powders obtained in Examples 1 to 4 and Comparative Example 1 were put into a mold battery and pressed into sheets by applying a pressure of 2T with a press, then LPSC was added and a pressure of 3T was applied with a press, then an NCM811 positive electrode was placed at the solid electrolyte end and a pressure of 4T was applied, and finally a lithium-indium alloy was placed at the LPSC end and the mold battery was assembled.

[0087] The performance testing was mainly carried out with a Blue Power battery testing system, and the cycle performance and rate performance were tested in the voltage range of 3V - 4V.

[0088] Result analysis

[0089] (1) The Li 2.1 Al 0.1 Hf 0.9 Cl6 solid electrolyte material prepared in Example 1 was analyzed by scanning electron microscopy at low magnification as Figure 1 shown, and the analysis by scanning electron microscopy at high magnification was as Figure 2 shown. It can be seen that its surface morphology presents a polycrystalline structure. The solid electrolyte materials obtained in Examples 1 to 4 were analyzed by X-ray diffraction as Figure 3 shown. It can be seen that the peak intensities at 32° and 43° gradually weakened with the increase of the amount of doped Al, and a new peak appeared at 28°, which proved the replacement of the central cation.

[0090] (2) The solid electrolyte materials obtained in Examples 1 to 4 were subjected to impedance analysis, as Figure 4 shown. It can be seen that with the increase of the doping amount of Al, the impedance showed a trend of first decreasing and then increasing, indicating that the ionic conductivity showed a trend of first increasing and then decreasing, and reached the highest when the proportion of Al was 0.1.

[0091] (3) Assembly and performance testing of lithium-ion all-solid-state batteries

[0092] The solid electrolyte material powder obtained in Example 1 was put into a mold battery and pressed into sheets by applying a pressure of 2T with a press, then LPSC was added and a pressure of 3T was applied with a press, then an NCM811 positive electrode was placed at the solid electrolyte end and a pressure of 4T was applied, and finally a lithium-indium alloy was placed at the LPSC end and the mold battery was assembled.

[0093] The performance tests were mainly carried out using a Blue Power battery test system within the voltage range of 3V - 4V for cyclic performance and rate performance tests.

[0094] Li 2.1 Al 0.1 Hf 0.9 The charge - discharge curves of the all - solid - state battery with the Cl6 solid electrolyte material are as Figure 5 shown. It can be seen that the charge - discharge curves of the first five cycles almost overlap, proving that there is almost no capacity loss, and the Coulombic efficiency of the first cycle is 90.11%. The rate performance is as Figure 6 shown. It can be seen that when the battery is gradually increased from a rate of 0.1C to 0.6C, the capacity attenuation is very small, and when it returns from 0.6C to 0.1C, the capacity can still return to the initial capacity. The cycle stability is as Figure 7 shown. It can be seen that after 50 cycles, the capacity can still remain basically unchanged, and the capacity retention rate is 99.6%.

[0095] In summary, for the solid - state electrolyte material containing doped metal halide provided in the embodiments of the present application, the structural formula of the solid - state electrolyte material containing doped metal halide is such as Li 2+x Al x Hf 1-x Cl6, where 0.1 ≤ x ≤ 0.4. By optimizing the content of aluminum element and hafnium element in the solid - state electrolyte material, using the hetero - valent metal Al 3+ to partially replace Hf 4+ , although the lattice gap is reduced, more Li + enters the lattice, making the Li + transport efficiency higher, thereby achieving the purpose of improving ionic conductivity, capacity and cycle stability. And because the Al metal is rich in the earth's crust and has a low cost, it is beneficial to further reduce the production cost and can increase the wide application rate of the product.

[0096] The above are only the preferred embodiments of the present application and are not intended to limit the present application. Any modifications, equivalent replacements, and improvements made within the spirit and principle of the present application shall be included within the protection scope of the present application.

Claims

1. A doped-metal-containing halide solid electrolyte material, characterized in that, The structural formula of the doped-metal-containing halide solid electrolyte material is as follows: Li 2+x Al x Hf 1-x Cl6, where 0.1 ≤ x ≤ 0.

4.

2. The doped metal-containing halide solid electrolyte material according to claim 1, wherein In the halide solid electrolyte material containing doped metal, the molar ratio of Al element to Hf element is 0.1-0.4:0.6-0.

9.

3. The halide solid electrolyte material containing doped metal according to claim 2, wherein In the halide solid electrolyte material containing doped metal, the molar ratios of Al element to Hf element include 0.1:0.9, 0.2:0.8, 0.3:0.7, 0.4:0.

6.

4. The halide solid electrolyte material containing doped metal according to claim 1, wherein The doped-metal-containing halide solid electrolyte material includes Li 2.1 Al 0.1 Hf 0.9 Cl6, Li 2.2 Al 0.2 Hf 0.8 Cl6, Li 2.3 Al 0.3 Hf 0.7 Cl6, Li 2.4 Al 0.4 Hf 0.6 any one of Cl6.

5. A preparation method of a doped-metal-containing halide solid electrolyte material, characterized in that, It includes the following steps: Weigh a certain amount of lithium-containing compound, hafnium-containing compound, and aluminum-containing compound and perform the first ball milling treatment to obtain a first mixture; Perform the second ball milling treatment on the first mixture to obtain a halide solid electrolyte material containing doped metal.

6. The preparation method of the doped-metal-containing halide solid electrolyte material according to claim 5, wherein, In the step of the first ball milling treatment, it includes the following: After mixing the lithium-containing compound, the hafnium-containing compound, and the aluminum-containing compound, place them in a ball milling jar and perform manual first ball milling treatment for 30 minutes.

7. The preparation method of the doped metal-containing halide solid electrolyte material according to claim 5, characterized in that, In the step of the second ball milling treatment, it includes the following: After mixing the first mixture with a dispersant and ball milling beads, place them in a ball milling jar and perform the second ball milling treatment.

8. The preparation method of the doped-metal-containing halide solid electrolyte material according to claim 7, wherein, The rotation speed of the second ball milling treatment is 400-500 rpm, and the ball milling time is 10-12 hours.

9. The preparation method of the doped metal-containing halide solid electrolyte material according to claim 7, wherein The ball milling beads are selected from ZrO2 ball milling beads, and the ball-to-material ratio of the ZrO2 ball milling beads to the first mixture is 40:1-1.

2.

10. A solid-state battery, characterized in that, The solid-state battery includes a positive electrode material, a negative electrode material, a separator, and a solid electrolyte. Among them, the solid electrolyte is selected from the halide solid electrolyte material containing doped metal according to any one of claims 1-4 or the preparation method of the halide solid electrolyte material containing doped metal according to any one of claims 5-9.

Citation Information

Cited By

  • Solid-state battery composite positive electrode with ion conduction and capacity contribution functions and preparation method of solid-state battery composite positive electrode

    CN121885528A